Studies on Schismatoglottideae (Araceae) of Borneo LX: Preliminary notes on the Schismatoglottis Patentinervia Clade, including descriptions of three new species - Wong, Sin Yeng; Boyce, P.C; Aisahtul, binti Wardi (International Aroid Society, Inc., 2017)
A review of the Schismatoglottis Patentinervia Clade is presented. Six species are accepted, of which three are pre-existing – Schismatoglottis patentinervia Engl. (Kalimantan Barat: Melawi), S. pectinervia A. Hay (NE Sarawak: Mulu; Brunei) and S.retinervia Furtado (Sabah: Kinabalu) – and three are taxonomic novelties